COVID-19 no Brasil : os efeitos de sentido em torno de Jair Bolsonaro no Facebook - Alves, Willamis de Santana (2022)
The new Coronavirus presents and requires great challenges in the current socio-political, economic and cultural context, including for the current president of the country, since he occupies a position subject to the highest authority of the nation, so he needs to take measures with his allies in order to combat the spread of the disease. In this sense, the media is affected by the measures of political confrontation and the event of the pandemic, which makes speeches with different effects of meaning circulate on social networks, such as Facebook, which can signify the subject Jair Bolsonaro in different ways. In view of these facts, our study seeks to understand, through Discourse Analysis from a Pecheutian perspective, how the president subject is constructed during the Covid-19 pandemic on Facebook. From this, our selected corpora refer to speeches in circulation on Fanpages (specific Facebook pages for newspapers, programs and institutions) of G1 (Grupo Globo News Portal), Jornal Nacional, R7 Notícias and El País Brasil , which circulated, during the pandemic, different effects of meaning about the following events: declaration by the World Health Organization (WHO) that determines a pandemic on March 12, 2020; the departure of the ministers of health in Brazil, Luiz Henrique Mandetta on 04/16/2020, Nelson Teich on 05/15/2020 and General Eduardo Pazuello on 03/23/2021; and the reach of 100 thousand deaths from the disease in the country on 08/08/2020. In our analyses, we work with categories such as: subject, ideology, relations of meaning, interdiscourse, memory, imaginary formations, Discursive Formation and production conditions. To do so, we rely on approaches from authors such as Pêcheux (1990) and (1995), Orlandi (2000) and (2007), Althusser (1970), Maldidier (1997). Taking into account our analyses, we could see that Jair Bolsonaro is meant, in such events, as a governmental political-institutional rupture in the left-wing Discursive Formation.